Pengembangan Penghitungan Kapasitas Volume Oksigen Maksimal (Vo2max) Menggunakan Tes Lari 2,4 KM Berbasis Aplikasi Android - Haikal Millah; Ari Priana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to develop a calculation of the maximum oxygen volume capacity using a 2.4km run test based on an android application. The method in this study uses research and development (Research and Development). Samples taken from the data for application trials were 10 people who did the 2.4 km run test. The results of the application manually are no different. This android application has a tutorial feature that aims to use this application. In addition, there is a menu for calculating vo2max and physical fitness level values. The determination of the value of the level of physical fitness is based on the general category of non-athletes. Users can calculate vo2max calculation starting from 1 person and there is a menu to count up to 10 people at once. This application is equipped with a data store feature using the SQLite database, so users can store data on the results of a 2.4 km run test. With this application, it can help sports practitioners in conducting physical endurance tests using the 2.4 km running test. Keywords: Vo2max Calculation, Android Application, Running Test 2.4 KM